Studi Alternatif Perkuatan Desain Timbunan Pada Pekerjaan Proyek Pembangunan Jalan Tol Binjai-Pangkalan Brandan Sta 55+500 - Permana, Muhammad Yuanto; Lastiasih, Yudhi (Syntax Corporation, 2025)
Land acquisition in toll road construction is crucial for smooth construction. The lengthy land acquisition process often results in projects that have begun construction but still have some land that has not been acquired. This occurred in the Trans-Sumatra Toll Road Project, Binjai-Langsa Section, Binjai-Pangkalan Brandan STA 55+500. In this section, there are still public cemeteries that have not been acquired and are awaiting relocation to new locations. This situation disrupts the toll road construction process, necessitating the use of vertical embankments as an alternative to sloped embankments, which require lengthy land acquisition. The use of alternative embankment management methods is an effort to ensure the project is completed within the agreed timeframe. The use of alternative vertical embankment methods will require reinforcement planning for the embankment. Alternative reinforcement methods for vertical embankments include geotextiles, sheet piles, and Geoforce Segmental Retaining Walls. These methods could be an alternative to using vertical embankments due to land acquisition limitations. Geotechnical analysis was conducted using a geotechnical analysis aid program based on LEM to determine the requirements for the selected reinforcement method. In the case of this toll road construction, using geotextile reinforcement would require one layer of 200kN geotextile, a 13-meter-long concrete sheetpile, or a 2.5-meter-high, 50-meter-wide geoforce segmental wall.